Color tunable light-emitting diodes based on p+-Si/p-CuAlO2 /n-ZnO nanorod array heterojunctions - Ling, Bo (2011)
Wide-range color tuning from red to blue was achieved in phosphor-free p+-Si/p-CuAlO2/n-ZnO nanorod light-emitting diodes at room temperature. CuAlO2 films were deposited on p+-Si substrates by sputtering followed by annealing. ZnO nanorods were further grown on the annealed p+-Si/p-CuAlO2 substrates by vapor phase transport. The color of the p-CuAlO2/n-ZnO nanorod array heterojunction electroluminescence depended on the annealing temperature of the CuAlO2 film. With the increase of the annealing temperature from 900 to 1050 °C, the emission showed a blueshift under the same forward bias. The origin of the blueshift is related to the amount of Cu concentration diffused into ZnO.